Eco-Friendly Nature Of Fiber Materials And Its Process During Construction - S. Rajavelu (International Journal of Modern Agriculture, 2021)
This paper focuses on the environmentally friendly nature of fiber materials used in buildings. Micro cracks form in traditional concrete before the structure is filled due to the changes in volume and drying. As the structure is filled, the very small cracks spread and open up, are causing inelastic deformation in the concrete. The cementing of a concrete reinforced mixture of more or less uniformly dispersed small fibers is known as FR. During the mixing phase, a large no. of microfibers are distributed and scattered in the concrete and increasing the property of concrete in all ways. A concrete fiber was depending upon the cement composite component that has been produced recently. It has been successfully used in the building because of its good impact and frost resistance, permeability, flexural tensile, and strong resistance to spitting. It's a good way to improve the mortar's durability, shock tolerance, and conflict to reduce plastic cracking. There are several advantages of using these fibers. Steel fibers can increase structural strength while reducing the need for heavy steel reinforcement. The concrete's freeze-thaw tolerance has been strengthened. The concrete's durability is increased, resulting in smaller crack widths. To increase impact resistance, polypropylene and nylon fibers are used.